Alternatively spliced BobCAL transcripts alter curd morphotypes in a collection of Chinese cauliflower accessions. (1st October 2020) - Cao, Wenguang; Cao, Biting; Wang, Xuan; Bai, Jinjuan; Xu, Yong-Zhen; Zhao, Jianjun; Li, Xiaorong; He, Yuke; Hu, Shengwu
Abstract: The curd of cauliflower ( Brassica oleracea L. var. botrytis ) is a modified inflorescence that is consumed as a vegetable. Curd formation is proposed to be due to a mutation in the BobCAULIFLOWER ( BobCAL ) gene, but the genetic relationship between BobCAL variation and curd morphotypes remains obscure. To address this question, we collected and classified a collection of 78 cauliflower accessions into four subpopulations according to curd surface features: smooth, coarse, granular, and hairy curd morphotypes. Through the cDNA sequencing of BobCAL alleles, we showed that smooth and coarse accessions characterized by inflorescence meristem arrest presented a strong association with the 451T SNP ( BobCAL_T ), whereas granular and hairy accessions marked with floral organ arrest presented an association with 451G ( BobCAL_G ). Interestingly, all BobCAL alleles were alternatively spliced, resulting in a total of four alternative splice (AS) variants due to the retention of the fourth and/or seventh introns. Among accessions with BobCAL_G alleles, the total expression of all these AS variants in granular plants was almost equal to that in hairy plants; however, the expression of the individual AS variants encoding intact proteins relative to those encoding truncated proteins differed. Hairy accessions showed relatively high expression of the individual variants encoding intact proteins, whereas granular accessions displayed relatively low expression. In smooth cauliflower, the overexpression of the BobCAL_Ga variant caused an alteration in the curd morphotype from smooth to hairy, concurrent with an increase in the expression levels of downstream floral identity genes. These results reveal that alternative splicing of BobCAL transcripts is involved in the determination of cauliflower curd morphotypes. Abstract : Four types of curd morphotypes were characterized from a collection of 78 cauliflower accessions, from which 4 splice variants of BobCAL alleles were identified, and their relative expression levels were defined to determine curd morphotypes.